ChemInform Abstract: A Novel One‐Pot Synthesis of Carbazole‐1, 4‐quinones Through Pd‐Catalyzed Cyclocarbonylation, Desilylation and Oxidation Processes from 3‐Iodo‐2‐propenylindoles. Issue 31 (5th August 2014) - Fujii, Mami; Nishiyama, Takashi; Choshi, Tominari; Satsuki, Nanase; Fujiwaki, Takaya; Abe, Takumi; Ishikura, Minoru; Hibino, Satoshi
Abstract 3‐Iodo‐2‐propenylindoles (I) are easily prepared from corresponding indole‐2‐carbaldehydes and vinyl Grignard reagents.